KONFRONTASI PSIKIS TOKOH UTAMA PADA FILM PULANG SUTRADARA AZHAR KINOL LUBIS: ANALISIS PSIKOLOGI SASTRA - Arwansyah, Yanuar Bagas; Arianti, Ristiana Sukma; Septarianto, Tomi Wahyu (JURNAL SKRIPTA, 2024)
This research aims to determine the psychological confrontation of the main character in the film Pulang, directed by Azhar Kinoi Lubis, including: 1) What is the building structure in the film Pulang, directed by Azhar Kinoi Lubis? 2) What is the psychic coherence of the main character in the film Pulang, directed by Azhar Kinoi Lubis? This research uses a qualitative descriptive method, because the data obtained and the analysis used in this research are qualitative. Data collection techniques in this research used documentation, observation and previous research techniques. The data analysis techniques used in this research are listening, grouping, analyzing and drawing conclusions. The results of the research show that the analysis of the psychological confrontation of the main character in the film Pulang, directed by Azhar Kinoi Lubis, is: 1) the character of the main character in the film Pulang 2) the psychological confrontation of the main character in the film Pulang which includes the id, ego and super ego aspects of each character.